Effects of a virtual reality serious game training program on the cognitive function of people diagnosed with schizophrenia: A randomized controlled trial - Wang, Xu; Kou, Xiaomin; Meng, Xiandong; Yu, Jianying (Frontiers in Psychiatry, 2022)
Background Cognitive impairment persists through the course of schizophrenia and affects patients’ activities of daily living. Aim This study aims to investigate the effects of a virtual reality (VR) serious game training program on the cognitive function of people diagnosed with schizophrenia. Materials and Methods Sixty-four eligible people diagnosed with schizophrenia were recruited and randomly assigned to the intervention group (n = 31) and the control group (n = 33). The control group received standard psychiatric care. The intervention group was trained with an additional VR game twice a day for at least 10 days during hospitalization. Cognitive function was measured at enrollment and before discharge using the Brief Cognitive Assessment Tool for Schizophrenia. Results Compared with those of the control group, the results of the working memory (t = 3.463, Cohen’s d = 0.87, p = 0.001) and executive function (TMTA: Z = -2.272, Cohen’s d = 0.59, p = 0.023; TMTB:Z = -2.365, Cohen’s d = 0.62, p = 0.018) of the intervention group after intervention were significantly better. However, there was no significant difference in the results of social cognition (Z = -1.394, Cohen’s d = 0.35, p = 0.163) between the two groups. Conclusion Intensive active virtual reality serious game training in addition to standard psychiatric care can significantly improve working memory and executive function in people diagnosed with schizophrenia. Implications for Practice When helping improve the cognitive function of people diagnosed with schizophrenia, mental health professionals should identify cognitive domains to be enhanced and develop corresponding serious game training strategies.